Evaluating Reconciliation Process of Post-Reformation Interethnic Conflict in Sampit, Indonesia - Raharjo, Wahyu Arif; Fitriyani, Indah (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2023)
Interethnic conflict in Sampit erupted amidst the post-Reformation era in Indonesia between the Madurese and Dayak people, which caused casualties and displacements. Peaceful coexistence is prevailing between both people in Sampit nowadays, but discussion about this reconciliation process is still rare, and its significance is in understanding the region’s transformation. This study evaluates the reconciliation process as a stepping stone toward positive peace by examining the reconciliation process of interethnic conflict in Sampit using Hamber’s model of reconciliation, exploring whether it supports conditions for positive peace. This study employs library research followed by descriptive qualitative analysis of existing literature, journal articles, reports, and documents on this case study. It argues that the Declaration of Tekad Damai Anak Bangsa operates as conflict resolution, with victory secured by the Dayak people as the indigenous people. The absence of truth-telling or mutual acknowledgment of events, compounded by the exodus of most Madurese, left reconciliation incomplete. Justice and litigation processes were passed to preserve the current non-conflict situation, resulting in a reconciliation dominated by the Dayak community. Although reconciliation has occurred at the leadership level among ethnic and government figures, critical grassroots issues like truth-telling, displacement, and justice remain unresolved. It has created a fragile peace, where lingering resentment and unresolved grievances could threaten the region’s stability. The study highlights the importance of addressing these underlying issues to transform the prevailing negative peace into sustainable positive peace.